Faunistical notes on the hoppers (Homoptera Auchenorrhyncha) in vineyards in the province of Piacenza (Bollettino di zoologia agraria e bachicoltura, 2024)
A list is given of the Homoptera Auchenorrhyncha found in the course of a monitoring programme on Scaphoideus titanus Ball carried out with chromotropic traps in three vineyards in the Apennines near Piacenza between 1992 and 1994. The three vineyards examined are at Travazzano (Carpaneto), Ancarano (Rivergaro) and Albarola (Vigolzone), places on the slopes of the foothills in three different valleys (Chero, Trebbia and Nure, respectively) in the province of Piacenza in northern Italy. In the first two vineyards the ground was kept unweeded; in the third chemical weed-killer was used and the ground between the rows was worked with a mechanical plough. Insecticide treatment was carried out in none of the three vineyards. Samples of Auchenorrhyncha were taken both from the vine foliage and from the vegetation in the grassy borders by means of an entomological net and an aspirator. Altogether 29 species were collected, belonging to the following families: Cixiidae, Delphacidae, Issidae, Flatidae, Cercopidae, Cicadellidae. In the unweeded vineyards at Travazzano and Ancarano a greater range of fauna was found (particularly in the first, where 21 species of Auchenorrhyncha were listed) than in Albarola (only 9 species), which was weeded. The Flatid Metcalfa pruinosa (Say) and the Cercopid Philaenus spumarius (L.) were present in notable numbers, as among the Cicadellidae was S. titanus in all three vineyards, some other Deltocephalinae and the Typhlocybinae Empoasca vitis (Gothe) and E. decipiens Paoli. Some of the species collected, notably M. pruinosa, Ph. spumarius, Macrosteles quadripunctulatus (Kirschbaum), S. titanus,  Anoplotettix fuscovenosus (Ferrari), Allygus modestus Scott, Euscelidius variegatus (Kirschbaum), Euscelis incisus (Kirschbaum) and Psammotettix alienus (Dahlbom), are known of in the literature as possible phytoplasma carriers for certain botanical species. This research helped to draw a profile of the fauna of the vineyard agro-ecosystem in the province of Piacenza and to find out the distribution of species that could be responsible for the transmission of phytopathogenic agents.
Keywords: Auchenorrhyncha; vineyard; province of Piacenza